Agitation Depth and Reinforcement Treatment on Tribology Characteristics of Aluminium particulated Composite under the Stir Casting Method - Imanullah, Fahmi; Ilham Akbar, Hammar; Surojo, Eko; Ariawan, Dody; Pramudi, Ganjar (Engineering, Technology & Applied Science Research, 2025)
The stir casting process involves several key parameters, including agitation speed, agitation time, holding time, stirrer size and dimension, stirring position, and particle treatment. This study evaluates the effect of stirring depth and surface particle modification on the hardness and tribological properties of Al6061-Al2O3 composites. These composites were manufactured using the current method at a temperature of 720 oC, with an agitation speed of 600 rpm for 10 minutes. The reinforcement consisted of 6%wt Al2O3 particle, while 2.5%wt Mg was added as a wetting agent. The results indicate that the optimum stirrer depth was 30% of the molten metal height, leading to enhanced hardness (66.5 HBN ) and reduced specific wear rate (1.17x10-4 mm3/Nm). Additionally, the electroless coating treatment at a stirrer depth of 30% improved wettability, further increasing hardness, and lowered the specific wear rate (70.2 HBN and 1.10x10-4 mm3/Nm). These findings highlight the importance of stirrer depth optimization and surface modification techniques in enhancing the mechanical and tribological performance of Al6061-Al2O3 composites.